Adjuvant intensity modulated whole-abdominal radiation therapy for high-risk patients with ovarian cancer (International Federation of Gynecology and Obstetrics Stage III): first results of a prospective phase 2 study - Arians, Nathalie; Kieser, Meinhard; Benner, Laura; Rochet, Nathalie; Katayama, Sonja; Sterzing, Florian; Herfarth, Klaus; Schubert, Kai; Schneeweiss, Andreas; Sohn, Christof; Debus, Jürgen; Lindel, Katja (International journal of radiation oncology, biology, physics, 2017)
PURPOSE: To assess treatment tolerance and toxicity rates of consolidative whole-abdominal radiation therapy (WART) following cytoreductive surgery and carboplatin/paclitaxel chemotherapy in high-risk patients with advanced ovarian cancer (International Federation of Gynecology and Obstetrics stage III) using intensity modulated radiation therapy. METHODS AND MATERIALS: The OVAR-IMRT-02 study is a multicenter, single-arm, phase 2 trial. Twenty patients with optimally debulked ovarian cancer (International Federation of Gynecology and Obstetrics stage III) with complete remission after chemotherapy were treated with intensity modulated WART as a consolidation therapy. A total dose of 30 Gy in 20 fractions of 1.5 Gy was applied to the entire peritoneal cavity. The primary endpoint was treatment tolerability, defined as lack of any Common Terminology Criteria for Adverse Events grade 4 toxicity within 10 weeks after start of treatment; secondary objectives were acute and chronic toxicity, quality of life, rates of therapy disruption and abortion, and progression-free and overall survival. RESULTS: Intensity modulated WART resulted in excellent coverage of the whole peritoneal cavity, with effective sparing of all organs at risk. The primary analysis included all 20 enrolled patients, of whom 19 did not experience Common Terminology Criteria for Adverse Events grade 4 toxicity. Only 1 patient experienced acute grade 4 hematologic toxicity. Thus, the tolerability rate of intensity modulated WART was significantly higher than 70%. No gastrointestinal acute toxicities higher than grade 2 have been observed. During WART, mean global health status decreased by 18.1 points (95% confidence interval 7.1, 29.0). Six weeks after WART, global health status had already increased, with a mean score difference of 4.6 (95% confidence interval -11.1, 20.4) compared with baseline. Similar characteristics were observed for all function scale scores. CONCLUSION: Intensity modulated WART after aggressive surgery and carboplatin/paclitaxel chemotherapy is associated with an acceptable risk of acute toxicity and a treatment tolerability rate significantly higher than 70%. Together with our knowledge about clinical feasibility, meaning excellent coverage of the planning target volume and effective sparing of organs at risk, intensity modulated WART could offer a new therapeutic option for consolidation treatment of patients with advanced ovarian cancer.